REVOLUTIONIZING ECONOMIC COMPETITIVENESS WITH AI FORECASTING TOOLS - Absalamova Diyora Bo‘riboyevna; Absalamova Go‘zal Bo‘riboyevna; Kamalova Jamila Muxsinovna; Nematova Farangiz Sanjar qizi; Maxamedova Munisaxon Alisher qizi (European Science Publishing, 2025)
In an era marked by rapid technological advancements, the integration of Artificial Intelligence (AI) into various sectors has become increasingly prevalent. One such area witnessing significant transformation is economic forecasting. This paper explores the potential of AI forecasting tools in revolutionizing economic competitiveness. By leveraging vast datasets, machine learning algorithms, and advanced analytics, AI offers unprecedented capabilities to enhance decision-making, optimize resource allocation, and mitigate risks in the economic landscape.
Keywords: Machine Learning, economic forecasting, forecasting tools, generative AI.